Oxy-combustion characteristics as a function of oxygen concentration and biomass co-firing ratio in a 0.1 MWth circulating fluidized bed combustion test-rig. (1st April 2020) - Nguyen, Hoang Khoi; Moon, Ji-Hong; Jo, Sung-Ho; Park, Sung Jin; Seo, Myung Won; Ra, Ho Won; Yoon, Sang-Jun; Yoon, Sung-Min; Song, Byungho; Lee, Uendo; Yang, Chang Won; Mun, Tae-Young; et al.
Abstract: Oxy-combustion with a circulating fluidized bed (Oxy-CFBC) can facilitate the separation of high CO2 concentration and reduce emissions by biomass co-firing. This study investigated Oxy-CFBC characteristics such as temperature, solid hold-up, flue gas concentrations including CO2, pollutant emissions (SO2, NO, and CO), combustion efficiency and ash properties (slagging, fouling index) with increasing input oxygen levels (21–29 vol%), and biomass co-firing ratios (50, 70, and 100 wt% with domestic wood pellet). The possibility of bio-energy carbon capture and storage for negative CO2 emission was also evaluated using a 0.1 MWth Oxy-CFBC test-rig. The results show that combustion stably achieved with at least 90 vol% CO2 in the flue gas. Compared to air-firing, oxy-firing (with 24 vol% oxygen) reduced pollutant emissions to 29.4% NO, 31.9% SO2 and 18.5% CO. Increasing the biomass co-firing from 50 to 100 wt% decreased the NO, SO2 and CO content from 19.2 mg/MJ to 16.1 mg/MJ, 92.8 mg/MJ to 25.0 mg/MJ, and 7.5 mg/MJ to 5.5 mg/MJ, respectively. In contrast to blends of sub-bituminous coal and lignite, negative CO2 emission (approximately −647 g/kWth ) was predicted for oxy-combustion only biomass. Highlights: Oxy-combustion with a 0.1 MWth CFB was operated. Effect on the various O2 concentrations and biomass firing ratios investigated. Stable shift from air-to oxy-fired easily achieved above 90% (dry) CO2 flue gas. Oxy-fired NO and SO2 emissions lower than those of air-fired. CO2 negative emission from biomass-only oxy-firing expected (−647 g CO2 /kWth ).